2001
DOI: 10.1111/j.1745-6584.2001.tb02354.x
|View full text |Cite|
|
Sign up to set email alerts
|

Drawdown and Stream Depletion Produced by Pumping in the Vicinity of a Partially Penetrating Stream

Abstract: Commonly used analytical approaches for estimation of pumping-induced drawdown and stream depletion are based on a series of idealistic assumptions about the stream-aquifer system. A new solution has been developed for estimation of drawdown and stream depletion under conditions that are more representative of those in natural systems (finite width stream of shallow penetration adjoining an aquifer of limited lateral extent). This solution shows that the conventional assumption of a fully penetrating stream wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
119
0
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 130 publications
(124 citation statements)
references
References 22 publications
(37 reference statements)
0
119
0
5
Order By: Relevance
“…Analytical estimations of stream depletion were first proposed by Theis [4] and have since continued to be developed (e.g., [5][6][7][8][9][10]). However, Spalding and Khaleel [11] demonstrated that, despite their convenience, analytical approaches often fail to account for conditions that exist in natural steam-aquifer systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analytical estimations of stream depletion were first proposed by Theis [4] and have since continued to be developed (e.g., [5][6][7][8][9][10]). However, Spalding and Khaleel [11] demonstrated that, despite their convenience, analytical approaches often fail to account for conditions that exist in natural steam-aquifer systems.…”
Section: Introductionmentioning
confidence: 99%
“…For a given change in the head difference, a higher C leads to a greater degree of stream depletion and a lower C leads to a lesser degree of stream depletion [13,14]. The correlation between C and the stream depletion makes it an important model parameter in numerical stream depletion simulations (e.g., [9][10][11][12]18,19]). …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, three fitting parameters were used to reproduce the observed drawdown in the case of PT low and PT high : the hydraulic conductivity, K, the aquifer storativity, S, and streambed conductance, l, per unit stream length. In the case of the PT test in the absence of flow in Prairie Creek, the Theis (1935) model was used, and the number of fitting parameters reduces to two, namely K and S. The BZT model (Butler et al 2001) was used in the global cluster analysis for simulating a piecewise-homogeneous aquifer that accounts for the meandering stream architecture of the modern Prairie Creek deposits. In the BZT model, the aquifer consists of three parallel, infinite strips: one underneath the stream and one for each stream bank.…”
Section: Parameter Identificationmentioning
confidence: 99%
“…Model outline and hydrologic framework Hunt (1999) and Butler et al (2001) presented twodimensional models of stream-aquifer interactions as a correction to the two-dimensional Theis (1935) solution for drawdown in a homogeneous confined aquifer (in the following, these models will be referred to as Hunt and BZT models). This correction can be illustrated by the Hunt model for drawdown, s(x,y,t), as…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation